Improving Integration of Transportation Modes for Hinterland of Prigi Commercial Port, East Java Province, Indonesia - Priyambodo; Sabtohadi, Joko; Hamid, Abdul; Novianti, Diah; Momon; Gartika, Dewi; Suroso; Juniati, Herma; Rita; Setyawan, Dendy; Mutholib, Abdul; Akustia, Win (Transactions on Maritime Science, 2024)
Prigi Commercial Port was developed to bridge the economic gap between northern and southern regions of East Java Province. Therefore this research analyses the integration of transportation modes in hinterland region of Prigi Commercial Port. Data was collected from the research region and assessed using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results have shown the transportation modes in hinterland region of Prigi Commercial Port to be inadequate and partially achieved. The government took two steps and the first was associated with the preservation and improvement of the positive aspects of transportation mode integration, such as intermodal network availability, route clarity, transfer points across various networks, and time. The second step addressed the less satisfactory elements, such as the availability of primary modes, information, clarity schedule transparency, fare details, clear timing information, and modes connection.